The Death Penalty in Florida - Slobogin, Christopher (2009)
This article summarizes the findings and recommendations of the ABA Death Penalty Moratorium Implementation Project's Florida Assessment Team, which I chaired. Relying on an analysis of caselaw, studies, news reports, and interviews, the article describes significant flaws in Florida's death penalty law and practice in nine areas: the police investigative process; the analysis of scientific evidence; the conduct of prosecutors; the qualifications, reimbursement and competence of defense attorneys; the decision-making process of judges; the structure and decision-making process of capital sentencing juries; clemency; the system's reaction to the race of the victim; and the treatment of people with mental disability. It also notes that administration of the death penalty in Florida is extremely expensive and thus may undermine the reliability of adjudications in noncapital cases